Effects of tulsi leaves and ginger solution on growth performance and hematological profiles of broilers (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was conducted to determine the efficacy of tulsi and ginger as a growth promoter in broilers. A total of thirty day old chicks (DOC) were purchased from CP Bangladesh Ltd. and after seven days divided into three groups (A), (B) and (C). No vaccination schedule was practiced and no antibiotics were added in ration. The (A) group was not supplemented with tulsi and ginger solution in drinking water. The (B) group was supplemented with tulsi solution @ 1ml/litre in drinking water and (C) group was supplemented with ginger solution @ 1 ml/litre in drinking water for consecutive 5 weeks started from 7th day of experiment. Weekly observations were recorded for live body weight gain up to 6th weeks and routine blood test was performed at 21st and 42nd days, to find out hematological changes between control and treatment groups. The FCR value of group (A) was 2.25, in group (B) was 1.99 and in group (C) was 1.90. From this initial study this may be concluded that production of broilers in by using tulsi and ginger was economic than control group. In Bangladesh broilers production is mainly organized by unemployed and its demand is very high because it supports marketing within 35–42 days. Short return of money but major problems is cost of production. The initial body weight (gm) of group (A), (B) and (C) on 7th  of day experiment were 168±8.54, 166±7.95 and 166±7.90 gm respectively and after 42nd day of experiment final body weight were 1561±12.10, 1698±12.87 and 1763±13.28 gm respectively. The net body weight gain were 1393±11.07, 1533±11.98 and 1588±12.10 gm respectively and economics of production were analyzed and found that net profit per broiler was 18.82, 36.13 and 42.53 Tk respectively. It is concluded that broiler production by using herbal extract may be profitable and suitable for human consumption.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 143-149